Eric H. Cline, 2014 1177 B.C.: The Year Civilization Collapsed, Turning Points in Ancient History Series, Princeton and Oxford: Princeton University Press, ISBN 9780691140896, xx+264pp, US$20. - Davey, Christopher J. (Buried History: The Journal of the Australian Institute of Archaeology, 2024)
None